Ijtihad dan Dinamika Hukum Islam - Abd. Salam Arief (UIN Sunan Kalijaga Yogyakarta, 2017)
By the beginning of the fourth century of Hijra (about AD 900), it was commonly accepted that the gate of ijtihad had become closed.This closing of the gate of ijtihad, as it was called taqlid. The while among of Muslim Jurists never regarded the gate of ijtihad as entirely closed, but the fact remains that development of Islamic law became progressively. Therefore, says Jalaluddin al-Suyuti, ijtihad isthe backbone of Syari„ah and withaout it no legal decisions can be reached. Ijtihad is the exertion of mental energy in the search for a legal opinion. In other words ijtihad is the maximum effort expended by the jurists to apply the principles and rules of usul al-Fiqh (legal theory) for the purpose of discovering God‟s law. The devolepments of Islamic law are considerable importence from several points of view. In the first place, they to be living system of law. Scoundly, they constitute a mirror of the course of social reform in the Muslim country. Thirdly, they provide a most sidelight on the progress of modernism in Islam, where theology and law largely go hand in hand: for the reforms do not only concern detailed practice but involve a number of the basic concepts of Muslim Jurisprodence.